Malalignment of the big toe nail in mother and child. - Chieco, P. (European Journal of Pediatric Dermatology, 2016)
Malalignment of the big toe nail, in this case present from the first months in the 3-year-old son and occurred at puberty in the mother, can be inherited as an autosomal dominant trait with variable penetrance. A clue to this malformation is the lateral deviation of the longitudinal axis of the nail plate as compared with that one of the distal phalanx (1). The two big toes are almost always involved even though often with different severity. The lateral deviation seems to be responsible for nail changes, with loss of transparency and of the rosy color, thickening of the nail plate with difficult cutting, furrows, ridges, onychomadesis, abnormal bending radius, onychogryphosis and sometimes ingrown toenail (2). As malalignment can improve or regress spontaneously a conservative treatment is indicated in mild cases; in severe cases surgical removal and realignment of the entire nail apparatus or just the destruction of the nail matrix can be attempted.